Subtype-Based Prognostic Analysis of Cell-in-Cell Structures in Early Breast Cancer - Zhang, Xin; Niu, Zubiao; Qin, Hongquan; Fan, Jie; Wang, Manna; Zhang, Bo; Zheng, You; Gao, Lihua; Chen, Zhaolie; Tai, Yanhong; Yang, Mo; Huang, Hongyan; et al. (Frontiers in Oncology, 2019)
Though current pathological methods are greatly improved, they provide rather limited functional information. Cell-in-cell structures (CICs), arising from active cell-cell interaction, are functional surrogates of complicated cell behaviors within heterogeneous cancers. In light of this, we performed the first subtype-based CICs profiling in human breast cancers by “EML” multiplex staining method, and accessed their values as prognostic factors by Cox univariate, multivariate and nomogram analysis. CICs were detected in cancer specimens but not in normal breast tissues. Totally 5 types of CICs were identified with one homotypic subtype (91%) and 4 heterotypic subtypes (9%). Overall CICs (oCICs) significantly associated with patient overall survival (OS) (P=0.011) as an independent protective factor (HR=0.423, 95% CI, 0.227-0.785; P=0.006). Remarkably, three CICs subtypes (TiT, TiM and MiT) were also independent prognostic factors. Among them, higher TiT, from homotypic cannibalism between tumor cells, predicted longer patient survival (HR=0.529, 95% CI, 0.288-0.973; P=0.04) in a way similar to that of oCICs, and that (HR=0.524, 95% CI, 0.286-0.962; P=0.037) of heterotypic TiM (tumor cell inside macrophage); conversely, the presence of MiT (macrophage inside tumor cell) predicted death hazard of 2.608 (95% CI, 1.344-5.063; P=0.05). Moreover, each CICs subtype tended to preferentially affect different categories of breast cancer, with TiT ((P<0.0001) and oCICs (P=0.008) targeting luminal B (Her2+), TiM (P=0.011) targeting HR- (Her2+/HR- and TNBR), and MiT targeting luminal A (P=0.017) and luminal B (Her-) (P=0.006). Furthermore, nomogram analysis indicated that CICs impacted patient outcomes in contributions comparable (for oCICs, TiT and TiM), or even superior (for MiT), to TNM stage and breast cancer subtype, and incorporating CICs improved nomogram performance. Together, we propose CICs profiling as a valuable way for prognostic analysis of breast cancer, and that CICs and their subtypes, such as MiT, may serve as a type of novel functional markers assisting clinical practices.